If u=(fog)(x) and v=(gof)(x), verify if u'=v'? f(x)=3x+2,g(x)=x^2+1
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,551 answers
starTop subjects are Math, Science, and Business
We have the functions f(x) = 3x+ 2 and g(x) = x^2 + 1
u = fog ( x) = f(g(x))
=> f(x^2 + 1)
=> 3(x^2 + 1) + 2
=> 3x^2 + 3 + 2
=> 3x^2 + 5
v = gof(x) = g(f(x))
=> g( 3x + 2)
=> (3x + 2)^2 +1
=> 9x^2 + 4 + 12x + 1
=> 9x^2 + 12x + 5
u' = 6x
v' = 18x + 12
Therefore u' is not equal to v'.
Related Questions
- Verify that f(x)=-2f'(x)-f"(x) if f(x)=(3x+1)*e^-x
- 1 Educator Answer
- Verify if limit of ln(1+x)/x is 1, x-->0
- 1 Educator Answer
- Evaluate the limit of the fraction (f(x)-f(1))/(x-1), if f(x)=1+2x^5/x^2? x->1
- 1 Educator Answer
- Verify the relation f'(x)/f(x)=1+lnx, if f(x)=e^(ln((x)^x))?
- 1 Educator Answer
- Where is the function f(x) discontinuous? f(x) = (x^2-x-2)/(x-2), if x is not 2 f(x) = 1, if x=2
- 1 Educator Answer
The answer is very simple: the derivatives of the functions u and v are not equal.
Since we know that the composition of 2 functions is not commutative, then the derivatives of 2 expressions that are not matching, are not equal.
We'll see how it happens.
We'll compose (fog)(x) = f(g(x))
We'll substitute x by g(x), in the expression of f(x).
f(g(x)) = 3(x^2 + 1) + 2
We'll remove the brackets:
f(g(x)) = 3x^2 + 5
u(x) = f(g(x))
We'll differentiate with respect to x:
u'(x) = 6x
Now, we'll compose (gof)(x) = g(f(x))
We'll substitute x by f(x), in the expression of g(x).
g(f(x)) = (3x + 2)^2 + 1
We'll expand the square:
g(f(x)) = 9x^2 + 12x + 4 + 1
g(f(x)) = 9x^2 + 12x + 5
v(x) = g(f(x))
We'll differentiate with respect to x:
v'(x) = 18x + 12
We can see that the expression of u'(x) = 6x and the expression of v'(x) = 18x + 12 are not equal.
Student Answers